The Impact of Client Evaluation to the Bank Services Quality in Keep Dealing With (مجلة المنصور, 2023)
The current study intend to make the acquaintance of banks clients evaluation impact on the levels of Bank services quality that they get, by attaining the best scales for measuring the bank service quality in Iraq by applying those scales on a chosen sample selected from domestic banks. In order to attend the gap between the client prospects about the service level and the actual service levels that he considers , a hundred application forms has been distributed, and only eighty three has been collected back, as ( 83%) of them. The study arrives at the client concerns on each service quality dimension to decide the level of the service quality which they get Moreover a strong relationship of statistical significant between the clients satisfaction and the Banks service quality , was found, The clients depend on the quality evaluation they make in keep cooperating and increase the loyalty to the banks they deal with. The study recommended to :-1- increase the trust between the Bank and its clients in dealing with each another.2- Make Applied studies to recognize the standards of bank services that the clients consider and attain their complete satisfaction by providing high level of services that surpass their expectation and give training courses to the service providers who has a direct contacts with Bank clients, to assure that .